Effectiveness of Cognitive Behavioral Therapy on Multi-drug Resistant Tuberculosis Patients in Mongolia: 10 years experiences - Dashdavaa, Dorjmaa; Rash, Bolor; Khuyagaa, Ser-Od; Purevdagva, Anuzaya; Oh, Kyung Hyun; Davaasuren, Oyunsuren; Dambaa, Naranzul; Oidov, Baatarkhuu; Zuunnast, Khishigsuren (Central Asian Journal of Medical Sciences, 2024)
Objective: During multidrug-resistant tuberculosis (MDR-TB) treatment, patients face depression and anxiety. This study aims to evaluate the effects of cognitive behavioral therapy (CBT) on the psychological status and risk of loss to follow-up (LTFU) during MDR-TB treatment in Mongolia. Method: Eligible participants were randomly assigned to intervention and control groups. Intervention group participants underwent CBT, while control group participants received standard patient education. Psychological status was assessed before and after CBT. MDR-TB treatment outcomes were evaluated as internationally defined. Results: The study included a total of 83 patients. After CBT, depression and anxiety levels decreased by 12% and 16%, respectively, in the intervention group, whereas the control group showed a 4% decrease in depression and an 8.5% increase in anxiety levels. MDR-TB treatment outcomes revealed an 8% higher treatment success rate and a fivefold reduction in LTFU rate in the intervention group compared to the control group. In multivariable logistic regression, risk factors associated with increased LTFU were living alone (OR 12.7, p=0.031) and not being provided CBT (OR 16.1, p=0.040). Conclusion: Our study suggests that CBT not only alleviates these psychological challenges but also diminishes the risk of LTFU during treatment, leading to improved MDR-TB treatment success.